INTEGRASI AGAMA DAN SAINS DALAM PERSPEKTIF ISMAIL RAJI AL-FARUQI - Umi Fitri Lestari; Eva Dewi; Maini Wati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The integration between religion and science has become one of the important themes in the study of modern thought, especially in the context of the Islamic world. Ismail Raji Al-Faruqi, a prominent Muslim thinker, presented a unique perspective on the relationship between these two fields. In this journal, Al-Faruqi's approach to the integration of religion and science will be discussed, as well as its implications for thought and practice in society. Through the analysis of Al-Faruqi's works and relevant data, it is hoped that a deeper understanding of the importance of the synergy between religion and science in the contemporary context can be achieved. This research investigates Ismail Raji Al-Faruqi's thoughts on the integration of religion and science, particularly in the context of Islam. Data were collected from various primary and secondary literature related to Al-Faruqi's ideas, using qualitative methodology. Research shows that Al-Faruqi placed tawhid (monotheism) as an important foundation for integrating religion and science. According to him, knowledge is Islamized by combining Islamic values with modern science. He emphasized that science and religion complement each other in the effort to draw closer to God, rather than being in conflict.